The genome sequence of the Straw-barred Pearl moth, Pyrausta despicata Scopoli, 1763 [version 1; peer review: 2 approved] - Gavin R. Broad; Douglas Boyes; David C. Lees (Wellcome Open Research)
We present a genome assembly from a male specimen of Pyrausta despicata (Straw-barred Pearl; Arthropoda; Insecta; Lepidoptera; Crambidae). The genome sequence has a total length of 481.83 megabases. Most of the assembly (99.61%) is scaffolded into 31 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled, with a length of 15.29 kilobases.